Exploring moral quandaries: An interpretative phenomenological inquiry into the ethical dilemmas faced by Emergency Medical Technicians (EMTs) in the Southern Philippines - Raifa M. Guro; Asnorah P. Hadji Ali; Ashley A. Bangcola; Monalinda M. Macawadib; Norhanie A. Ali; Alibasher D. Macalnas (Belitung Raya Foundation, 2024)
Background: Emergency Medical Technicians (EMTs) in Lanao del Sur, Philippines, face ethical dilemmas shaped by the Meranao cultural value of 'Maratabat,' which emphasizes family honor and dignity. Understanding these cultural nuances is crucial for improving emergency medical care and addressing the ethical challenges encountered by EMTs in this region. Objective: This study aimed to explore the ethical dilemmas experienced by EMTs in disaster management settings, particularly how cultural values shape their decision-making processes. Methods: A phenomenological design was utilized. Eight EMTs working at the Provincial Disaster Risk Reduction and Management Office (PDRRMO) of Lanao del Sur, Philippines, were purposefully selected to participate. Data were collected from 31 January 2024 to 1 February 2024 through in-depth interviews, and thematic analysis was employed for data analysis. Results: Key themes emerged, including navigating complex dilemmas, adhering to organizational protocols, influential factors impacting EMTs' capacity to handle ethical dilemmas in emergency services, and coping strategies for EMTs in addressing the psychological burden from ethical dilemmas in emergency care. The concept of 'Maratabat' greatly affects EMTs' ethical decision-making processes, guiding their actions in the field. Conclusion: The study highlights the importance of cultural values, organizational backing, and coping mechanisms in effectively enabling EMTs to address moral quandaries in their professional roles. Institutional support, a positive organizational culture, and continuous education are essential in assisting EMTs in making informed decisions amid ethical dilemmas. These findings have implications for interventions and strategies to support EMTs as frontline providers of emergency medical services, enhancing patient care quality during crises.